Discrimination among varieties of Triticum turgidum subspecies (dicoccon, turanicum and durum) based on the fatty acid profile. (May 2021) - Tavoletti, Stefano; Pasquini, Marina; Mozzon, Massimo; Servadio, Davide; Merletti, Ariele; Mannozzi, Cinzia; Foligni, Roberta
Abstract: Fatty acid (FA) profiles of one dicoccon (emmer), two turanicum and seven durum varieties of Triticum turgidum, including two old durum varieties (Senatore Cappelli and Taganrog), were evaluated at two different sowing seasons in a split-plot design. Univariate (Analysis of Variance, ANOVA) and multivariate (Linear Discriminant Analysis, LDA) were applied. Univariate analysis discriminated the emmer wheat variety due to its high oleic, arachidic and eicosenoic acids and low linoleic and linolenic acids. The n-6/n-3 ratio discriminated the three subspecies (dicoccon vs turanicum vs durum). LDA allowed to further discriminate all varieties among each other. In particular, the old durum Senatore Cappelli was clearly discriminated from modern ones, whereas Taganrog was closer to them. Nutritional parameters confirmed the high quality of fatty acid profile of all varieties due to the prevalence of unsaturated fatty acids, but the high n-6/n-3 ratio suggested that these cereals must be included in diets enriched of n-3 fatty acids. Variety ' Sowing Season interaction was detected mainly by LDA approach. Overall, univariate and LDA supplied complementary information on variability of fatty acid contents among and within T. turgidum subspecies. Graphical abstract: Image 1 Highlights: FA profile discriminated T. turgidum ssp. dicoccon, turanicum and durum varieties. Oleic, linoleic, α-linolenic arachidic, eicosenoic FAs discriminated emmer wheat. The n-6/n-3 ratio discriminated the three T. turgidum subspecies. Mainly vaccenic & linoleic FAs discriminated old Senatore Cappelli vs. modern durum . The old durum variety Taganrog showed the closest FA profile to modern varieties.